The Future of India's Social Safety Nets - Rahman, Andaleeb; Pingali, Prabhu (Springer Nature, 2024)
India has learned what to do and what not to do when it comes to implementing policy to address human suffering. The COVID-19 pandemic unified the international response in similar ways, and the world has a lot to learn about key initiatives in India that have been implemented since India's independence. This open-access book includes key learnings about the conceptualization, design, and impact of social welfare programs in India spanning more than a 75-year period. The Future of India's Social Safety Nets provides a comprehensive analysis of these systems by combining insights from a wealth of interdisciplinary scholarship on social protection, economic development, and social policy. It covers India’s social development in terms of three essential aspects of policy design: focus (intended beneficiaries), form (transfer modalities), and scope (developmental objectives). Highlighting the developmental achievements and shortcomings of the myriad of social welfare schemes, this book proposes a framework to foster human resilience through social protection. This is an open-access book.